Responsive dissemination: A data driven approach to change - Sherry, L.; Gibson, David (AACE, 2005)
Reforms and innovations showing promise in initial test bed settings often founder when brought to a wider audience (Sabelli & Dede, 1999). The TEN Project, a 2000 PT3 Catalyst Grant, confronted the challenge of scaling and sustaining their work by developing and implementing a theory of responsive dissemination. Responsive dissemination integrates the principles and practices of a successful innovation with the varied contexts and settings to which such an innovation might be scaled. In this paper, we illustrate how implementation of TEN’s flexible electronic toolsets using the responsive dissemination model supported educational renewal in several programs and institutions while retaining fidelity to TEN’s initial principles for infusing technology into teacher education reform; and we offer guidelines for the model’s wider application.